Limb apraxia in aphasic patients - Ortiz, Karin Zazo [UNIFESP] (2017)
Limb apraxia is usually associated with left cerebral hemisphere damage, with numerous case studies involving aphasic patients. The aim of this study was to verify the occurrence of limb apraxia in aphasic patients and analyze its nature. This study involved 44 healthy volunteers and 28 aphasic patients matched for age and education. All participants were assessed using a limb apraxia battery comprising subtests evaluating lexical-semantic aspects related to the comprehension/production of gestures as well as motor movements. Aphasics had worse performances on many tasks related to conceptual components of gestures. The difficulty found on the imitation of dynamic gesture tasks also indicated that there were specific motor difficulties in gesture planning. These results reinforce the importance of conducting limb apraxia assessment in aphasic patients and also highlight pantomime difficulties as a good predictor for semantic disturbances.